2014
DOI: 10.1103/physrevd.89.064034
|View full text |Cite
|
Sign up to set email alerts
|

On the renormalization of the Gibbons-Hawking boundary term

Abstract: The bulk (Einstein-Hilbert) and boundary (Gibbons-Hawking) terms in the gravitational action are generally renormalized differently when integrating out quantum fluctuations. The former is affected by nonminimal couplings, while the latter is affected by boundary conditions. We use the heat kernel method to analyze this behavior for a nonminimally coupled scalar field, the Maxwell field, and the graviton field. Allowing for Robin boundary conditions, we examine in which cases the renormalization preserves the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…To our knowledge, no literature has mentioned this kind of treatment regarding a gauge field action in curved spacetime with boundary. (See, for example, [29], [30] for different approaches. )…”
Section: Gauge Fields In Curved Spacetime With Boundary Revisitedmentioning
confidence: 99%
“…To our knowledge, no literature has mentioned this kind of treatment regarding a gauge field action in curved spacetime with boundary. (See, for example, [29], [30] for different approaches. )…”
Section: Gauge Fields In Curved Spacetime With Boundary Revisitedmentioning
confidence: 99%
“…We would have to add matter fields to the truncation ansatz [82][83][84][85] and include for all types of fields the corresponding (Gibbons-Hawking, etc.) surface terms that are needed on spacetimes with a non-empty boundary [50,86].…”
Section: Jhep03(2015)065mentioning
confidence: 99%
“…The fact that the physical states are associated with the hypersurface in the boundary region brings along the issue of boundary conditions: for quantization and various quantum-level analyses, a systematic analysis of the boundary conditions is highly desirable. Earlier works and reviews can be found, e.g., in [25][26][27][28][29][30][31]. As we will see, non-Dirichlet boundary conditions, in particular Neumann-type boundary conditions, will play an important role in the complete quantum description of the system.…”
Section: Introductionmentioning
confidence: 85%
“…The analysis is not only meaningful in its own right but should also precede certain quantum-level manipulations such as partial integrations performed on the quantum-level action. There exists extensive literature on symmetry-preserving boundary con-ditions, see, e.g, [25][26][27][28][29][30][31] and refs therein. The issue of the gauge invariant boundary terms turns out to be highly nontrivial although it is possible to come up with such boundary terms and carry out more rigorous analysis in certain cases.…”
Section: Boundary Conditions and Dynamicsmentioning
confidence: 99%